Case Study: The Shtokman Project - Kovalevskaya, Daria; Mikhaylova, Olga (2011)
This research is conducted on one of the world’s largest deposits - Shtokman gas and condensate field located in the Barents Sea. The development of the field is operated by the Special Purpose Company Shtokman Development AG - the international consortium of Total, Statoil and Gazprom.